Evaluasi Keamanan Informasi pada Dinas Komunikasi dan Informatika Kabupaten Malang menggunakan Indeks KAMI (Keamanan Informasi) - Nabilla Diva Ramadhani; Widhy Hayuhardhika Nugraha Putra; Admaja Dwi Herlambang (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
Dinas Komunikasi dan Informatika (DISKOMINFO) Kabupaten Malang is a governmental institution located in Malang Regency that focuses on the communication sector and informatics sector and also providing the public services based on information technology. Regarding the importance of information security, Kementerian Komunikasi dan Informatika made a Ministerial Regulation No. 4 of 2016 about Information Security Management Systems to support information security at governmental institution. Correlating to these regulations, as an government institution that runs on the field of information, evaluation of the level of information security is needed. In this study, the evaluation was carried out using the tools or instruments based on Information Security Index (KAMI) 4.0 which can indicate the level of preparedness and maturity of information security in government institution. The evaluation results show the level of completeness of information security obtained a score of 195 and the average level of information security maturity level at level I and level I +. The results that obtained based on the KAMI index guidelines that is Dinas Komunikasi dan Informatika Kabupaten Malang is needed to increase the level of eligibility to certify ISO 27001. As the consequence, there are 17 recommendations are generated on governance area, 16 recommendations on risk management area, 27 recommendations on framework area, 31 recommendations on asset management area, 6 recommendations on technology and information security area, and 9 recommendations on supplements area that proposed to the DISKOMINFO Kabupaten Malang to complete the application of information security.